A year of COVID-19: effects of a global pandemic on a hip fracture bundled care protocol - Khai Cheong Wong; Kenny Xian Khing Tay; Suang Bee Koh; Tet Sen Howe (Singapore Medical Journal)
Introduction: Our aim was to analyse how the coronavirus disease 2019 (COVID-19) pandemic affects a hip fracture bundled care protocol. We hypothesised that key performance indicators, but not short-term outcomes, may be adversely affected. Methods: Patients admitted under a hip fracture bundled care protocol were divided into two arms: ‘COVID’ group included patients admitted in 2020 during the COVID-19 pandemic and ‘PRE-COVID’ group included patients admitted in 2019. We retrospectively analysed time to admission, time to surgery, length of stay, discharge disposition, as well as rates of 30-day revision surgery, 30-day readmission and inpatient mortality. Results: There were 307 patients in the PRE-COVID group and 350 patients in the COVID group. There was no significant difference in terms of gender, age and type of hip fracture. The COVID group had a higher proportion of American Society of Anesthesiologists classification III and IV patients (61.4% vs. 50.2% in the PRE-COVID group; P = 0.004). In the COVID group, similar proportion of patients were admitted to the ward within 4 h, but the mean time to surgery was longer (71.8 ± 73.0 h vs. 60.4 ± 72.8 h in the PRE-COVID group; P = 0.046) and few patients underwent operations within 48 h (41.7% vs. 60.3% in the PRE-COVID group; P < 0.001). Mean postoperative length of stay, discharge disposition, as well as rates of inpatient mortality, 30-day revision surgery and 30-day readmission were similar. Conclusion: The volume of hip fractures during the COVID-19 pandemic remained unchanged, although patients admitted during the COVID-19 pandemic appeared to be more deconditioned. Nevertheless, having robust protocols and staff familiar with hip fracture treatment can preserve short-term outcomes for this group of patients, even with strict isolation measures in place during a pandemic.